Monochoroterpes, a replacement name for Monophyllus Kluge, 2012 (Insecta: Ephemeroptera), nec Monophyllus Leach, 1821 (Mammalia: Chiroptera) - Kluge, Nikita J.; Jacobus, Luke M. (Zootaxa, 2015)
The genus group name Monophyllus Kluge, 2012 was established to include a single species of the mayfly family Leptophlebiidae (Insecta: Ephemeroptera) from Hainan Island, China, Choroterpes (Monophyllus) monophyllus Kluge, 2012. Unfortunately, this name is preoccupied by Monophyllus Leach, 1821, a genus of Phyllostomidae bats (Mammalia: Chiroptera) from the Antilles (type species: M. redmani Leach, 1821: 76). Therefore, we propose a replacement name for the mayfly genus group as follows.